2007
DOI: 10.5338/kjea.2007.26.4.300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Winter Rye Cultivation to Improve Soil Fertility and Crop production in Alpine Upland in Korea

Abstract: 농촌진흥청 고령지농업연구소, ABSTRACT: Soil erosion is one of the most serious problems in alpine upland in Korea. Soil fertility has continuously decreased due to serious soil erosion. To increase soil fertility, new sources of organic matter should be inputted. Therefore, the objectives of this research were to select winter cover crop as new sources of organic matter and to investigate the effect of winter cover crop on soil property changes, major crop productivity (Chinese cabbage, potato) production in highland, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Population structure is an important factor for ensuring crop production. Reasonable planting density can alleviate the stresses between individuals and the group and promote the coordinated development of spike number per unit area, grain number per spike, and thousand-grain weight [5]. Keles, et al [6][7][8][9] showed that with an increase in planting density, rye yield first increases and then decreases, while the total tiller number, plant height, and stem leaf ratio increase gradually with an increase in planting density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population structure is an important factor for ensuring crop production. Reasonable planting density can alleviate the stresses between individuals and the group and promote the coordinated development of spike number per unit area, grain number per spike, and thousand-grain weight [5]. Keles, et al [6][7][8][9] showed that with an increase in planting density, rye yield first increases and then decreases, while the total tiller number, plant height, and stem leaf ratio increase gradually with an increase in planting density.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the optimum planting density and planting schedule of winter rye requires an in-depth study [18]. To establish the best planting plan for overwintering rye in high-latitude areas, and to explore the physiological basis of yield formation under different planting densities, the physiological characteristics, stem morphological characters, aging characteristics, and feeding quality of winter rye under different planting densities were studied [5]. This study provides a practical reference for establishing the production mode of winter rye feeding and for resolving the quality problems of rye cultivation in early spring cold forages by establishing the optimal planting density of early spring rye and winter forage in cold regions.…”
Section: Introductionmentioning
confidence: 99%
“…연작장해는 동일토양에 동일작물을 연속적으로 재배하여 재배연수가 늘어남에 따라 여러 가지 원인에 의해 작물의 생 산량이 감소하고 품질이 떨어지는 현상을 말한다 [9]. 연작장 해의 발생원인에 관해 현재까지 발생기작이 확실하게 구명되 지 않았지만, 토양물리•화학성의 변화에 따른 양분의 불균형, 토양 pH와 물리성의 악화, 토양미생물상의 변화, 토양병원균 의 집적, 독소물질의 잔류 등이 연작장해의 원인으로 알려져 있다 [10]. 연작장해는 화학적 요인과 생물적 요인으로 나눌 수 있는데 이들의 관계를 보면, 비료의 남용은 토양 내 양분 과잉을 초래하고 토양양분의 불균형과 pH 상승으로 이어져 작물의 흡수장해를 일으킨다.…”
unclassified